Electronic Certificates in Indonesia: Enhancing Legal Certainty or Introducing New Challenges? - Putri Diyah Ayu Anggraini; Aqhina Dzikrah Aurora; Aprilia Niravita; Muhammad Adymas Hikal Fikri; Harry Nugroho (Arkus, 2025)
The Indonesian government is moving towards digital transformation in land administration by introducing electronic certificates (e-certificates) through the Regulation of the Minister of ATR/BPN Number 1 of 2021. This initiative aims to improve the security and legal certainty of land ownership, building upon existing programs like the Complete Systematic Land Registration Program (PTSL). This study used a normative legal research method to investigate the opportunities and challenges associated with implementing e-certificates in Indonesia. Primary legal sources, such as the Electronic Information and Transactions Law (UU ITE) and relevant ministerial regulations, were analyzed. Secondary data from legal journals, academic publications, and theses were also examined. The study revealed that e-certificates offer several advantages, such as increased efficiency in land administration, potential integration with blockchain technology, and improved land mapping and survey processes. However, challenges remain, including cybersecurity risks, limited technological infrastructure, and the digital literacy gap. Furthermore, the legal status of e-certificates as evidence in court, while recognized by the Ministry of ATR/BPN and UU ITE, requires further clarification within the Indonesian legal framework. This study concludes that e-certificates hold the potential to modernize land administration and enhance legal certainty in Indonesia, but successful implementation requires addressing critical challenges and ensuring comprehensive legal and regulatory clarity.